TRANSACTIONAL POLITICS AND RECIPROCITY AT THE LOCAL LEVEL: AN ANALYSIS OF THE 2024 SIDIKALANG ELECTION - Pairus Ayainas Pinem; Elly Warnisyah Harahap (SOSIOEDUKASI, 2025)
This study aims to analyze the political practice of reciprocating in the 2024 Regional Elections in Sidikalang District and the factors that affect it. By using a qualitative approach and in-depth interview techniques with various informants such as success teams, community leaders, voters, and party administrators, it was found that the practice of reciprocating favors is the main strategy in building political support. The politics of reciprocity is carried out through the provision of social assistance, promises of projects, and the strengthening of ethnic or religious ties. The main factors driving this practice are patron-client relations, weak political education, party pragmatism, and the dominance of clienteleistic strategies in campaigns. These findings show that local democracy is still colored by transactional relations that hinder the formation of a government that is oriented towards the public interest. Therefore, efforts to improve political literacy, party reform, and law enforcement against money politics are needed to encourage a cleaner and more integrity election process.